(untitled) (UNIZIK Journal of Marketing, 2024)
Customer advocacy has compelling evidence in the business sector that may influence prospective customers to purchase a company’s products and services. It is a recommendation of a product, service, or brand based on its performance that spreads by word-of-mouth. The insurance penetration in Nigeria, which is less than 1%, reflects a lack of client advocacy for insurance. Disseminating favorable information based on user experience impacts purchasing decisions, leading to increased revenue and profitability. The present research seeks to determine the impact of relationship marketing (RM) characteristics on consumer advocacy. The study used a survey research design. The survey included 375,000 estimated insurance service consumers in Lagos State, Nigeria. A sample of 1,650 customers was picked from certain Local Government Areas in Lagos State using a non-probability sampling method. An adapted and validated questionnaire on relationship marketing and market penetration in the insurance industry was used. The Cronbach’s Alpha coefficient for the constructions varied from 0.76 to 0.90. A total of 1,650 questionnaires were distributed, and 80% of them were completed and returned. The data were examined using descriptive statistics and multiple regression analysis for inferential statistics. The study indicates that relationship marketing has a substantial impact on customer advocacy in the insurance sector. The research recommends that insurance professionals should use relationship marketing as a strategy to impact customer advocacy in the insurance industry